Optimization and in vivo toxicity evaluation of G4.5 PAMAM dendrimer-risperidone complexes - Prieto, Maria Jimena (2014)
Risperidone is an approved antipsychotic drug belonging to the chemical class of benzisoxazole. This drug has low solubility in aqueous medium and poor bioavailability due to extensive first-pass metabolism and high protein binding (.90%). Since new strategies to improve efficient treatments are needed, we studied the efficiency of anionic G4.5 PAMAM dendrimers as nanocarriers for this therapeutic drug. To this end, we explored dendrimer-risperidone complexation dependence on solvent concentration, pH and molar relationship. The best dendrimer-risperidone incorporation (46 risperidone molecules per dendrimer) was achieved with a mixture of chloroform:methanol 50:50 v/v solution pH 3. In addition, to explore the possible effects of this complex,in vivo studies were carried out in the zebrafish model. Changes in the development of dopaminergic neurons and motoneurons were studied using tyrosine hydroxylase and calretinin, respectively. Physiological changes were studied through histological sections stained with hematoxylin-eosin to observe possible morphological brain changes. The most significant changes were observed when larvae were treated with free risperidone, and no changes were observed when larvae were treated with the complex.